2x+3(x+17)=-9

Simple and best practice solution for 2x+3(x+17)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(x+17)=-9 equation:


Simplifying
2x + 3(x + 17) = -9

Reorder the terms:
2x + 3(17 + x) = -9
2x + (17 * 3 + x * 3) = -9
2x + (51 + 3x) = -9

Reorder the terms:
51 + 2x + 3x = -9

Combine like terms: 2x + 3x = 5x
51 + 5x = -9

Solving
51 + 5x = -9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-51' to each side of the equation.
51 + -51 + 5x = -9 + -51

Combine like terms: 51 + -51 = 0
0 + 5x = -9 + -51
5x = -9 + -51

Combine like terms: -9 + -51 = -60
5x = -60

Divide each side by '5'.
x = -12

Simplifying
x = -12

See similar equations:

| 8x+3=515 | | 2x+3(x-17)=-9 | | 10.8x-30.7=-66.5 | | 10.8-30.7=-66.5 | | 4x+4=x+8 | | f=3964.50-3695 | | 2x^2-4=68 | | 4n+1/3(9n-33)=10 | | 35b^2+b-6=0 | | i=40000*0.67*2 | | z^2=17-52 | | 3w^2-.75=.5 | | 10000=18.76+22.43 | | .5c^2+2c+.75=0 | | -3(4v-2)+9v=6(v+3) | | 13-8x=2x-7 | | 27x^2-15x+2=0 | | 4y-2x=8x | | (X-30)(x+19)=0 | | 3u+9-8u=-31 | | -5(x*x)=20 | | 5x+2x=91 | | -5(x*x)=-80 | | 5y^3dx-y^2(-2x+x^4y^2)=0 | | 3(20+x)=5 | | 5x-2=10x-17 | | 12y-27=3y | | 142000000/1.11 | | -3(7x-3)=-75 | | y*y*y=1/27 | | 7x+3-(10x+2)=5+x | | 15x+47=-5x-1 |

Equations solver categories